2017
DOI: 10.1111/nph.14972
|View full text |Cite
|
Sign up to set email alerts
|

Stored root carbohydrates can maintain root respiration for extended periods

Abstract: Tight coupling between below-ground autotrophic respiration and the availability of recently assimilated carbon (C) has become a paradigm in the ecophysiological literature. Here, we show that stored carbohydrates can decouple respiration from assimilation for prolonged periods by mobilizing reserves from transport roots to absorptive roots. We permanently disrupted the below-ground transfer of recently assimilated C using stem girdling and root trenching and measured soil CO efflux for over 1 yr in longleaf p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 72 publications
6
37
0
Order By: Relevance
“…We show that longleaf pine savannas are resilient to the disturbance of fire and drought, as a result of their ability to rapidly mobilize nonstructural carbohydrates when photosynthate supply is low, in agreement with a previous study conducted at our sites (Aubrey and Teskey 2018). However, we found that the magnitude and timescale of recovery was site-dependent.…”
Section: Discussionsupporting
confidence: 92%
“…We show that longleaf pine savannas are resilient to the disturbance of fire and drought, as a result of their ability to rapidly mobilize nonstructural carbohydrates when photosynthate supply is low, in agreement with a previous study conducted at our sites (Aubrey and Teskey 2018). However, we found that the magnitude and timescale of recovery was site-dependent.…”
Section: Discussionsupporting
confidence: 92%
“…Twelve trees from each species between 20 to 25 cm dbh were randomly selected and inspected to ensure there were no diseases or obvious visible injuries that could have potentially affected the amount of carbon stored. Stem cores and coarse root samples were collected from the same individual trees in October and the following March, periods that reflect the seasonal minimum and maximum, respectively, for starch [3] which is the NSC component believed to play the largest role in storage [20]. We focused our belowground efforts on coarse roots because they represent the largest belowground storage reservoir-both in terms of overall mass and starch concentration-and they exhibit more dynamic seasonal patterns of accretion and depletion relative to the finest roots [3].…”
Section: Experimental Designmentioning
confidence: 99%
“…Under these circumstances, non-structural carbohydrates (NSCs) are mobilized to compensate for the insufficient supply of current photosynthate required to maintain the metabolism of existing cells as well as to refoliate the canopy, thereby decreasing the stored carbohydrate pool. This strategy of storing carbohydrates may provide an advantage for mature individuals experiencing frequent disturbances [1][2][3]. Alternatively, the advantage conferred by increased stored carbohydrate reserves under chronic disturbance could be a trait favored by selection at a critical life history stage that maintains benefits at later stages-a concept analogous to developmental inertia as described by Minelli [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…We estimated energy invested into growth by multiplying monthly biomass increments (kg m −2 ) with the proportional energy contents of cellulose, lignin, starch, and sugar. Starch and sugar content of nonstructural carbohydrate (NSC) contents of mature longleaf pine roots were measured during a study conducted at our sites during 2011 and 2012 (Aubrey & Teskey, ). Starch and sugar contents varied by season but were similar on an annual basis, as well as among sites, ranging from ~5–10% for starch and ~3–4% for sugars.…”
Section: Methodsmentioning
confidence: 99%